Sleep duration and insulin resistance in obese adolescents with metabolic syndrome: is there a correlation? - Widjaja, Nur Aisiyah; Kurube, Claudia Felisia; Ardianah, Eva (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Short sleep duration causes many changes in several hormones (leptin, ghrelin, insulin, cortisol, growth hormone) and increases sympathetic activity with elevated levels of catecholamines, which causes an energy imbalance and leads to overweight or obesity and insulin resistance. The present study aimed to analyze the relationship between sleep duration and insulin resistance in obese adolescents with metabolic syndrome. Methods: An observational cross-sectional research design concluded 124 obese adolescents with metabolic syndrome (MetS) aged 13-18 years. Anthropometry, blood pressure, and blood tests were conducted to determine obesity according to CDC 2000. MetS determination based on International Diabetes Federation 2007. Insulin resistance was assessed using HOMA-IR. Sleep duration was determined based on direct interviews with the research subjects. The obtained data were analyzed using the Spearman correlation test, Chi-Square, Mann-Whitney, and T-test (significant at P <0.05). Results: The subjects were dominated by male adolescents 67.5%. There was a strong relationship between age and sleep duration (p = 0.035). Subjects were divided into two age groups based on sleep duration: those with < 8 hours and > 8 hours of sleep. There was a significant difference in fasting insulin levels and HOMA IR value between the two groups, higher in the subjects with < 8 hours of sleep than the subjects with > 8 hours of sleep. Sleep duration and HOMA-IR values ​​as a marker of insulin resistance had a significant negative correlation (rs= -0.581; P <0.001) and insulin levels (rs=-0.565, P <0.001). Conclusions: Sleep duration has a robust negative correlation with the HOMA-IR value, which is a parameter of insulin resistance. (www.actabiomedica.it)